Length of Stay in Ambulatory Surgical Oncology Patients at High Risk for Sleep Apnea as Predicted by STOP-BANG Questionnaire. (16th August 2016) - Balachandran, Diwakar D.; Faiz, Saadia A.; Hernandez, Mike; Kowalski, Alicia M.; Bashoura, Lara; Goravanchi, Farzin; Cherian, Sujith V.; Rebello, Elizabeth; Kee, Spencer S.; French, Katy E.
Abstract : Background . The STOP-BANG questionnaire has been used to identify surgical patients at risk for undiagnosed obstructive sleep apnea (OSA) by classifying patients as low risk (LR) if STOP-BANG score < 3 or high risk (HR) if STOP-BANG score ≥ 3. Few studies have examined whether postoperative complications are increased in HR patients and none have been described in oncologic patients. Objective . This retrospective study examined if HR patients experience increased complications evidenced by an increased length of stay (LOS) in the postanesthesia care unit (PACU). Methods . We retrospectively measured LOS and the frequency of oxygen desaturation (<93%) in cancer patients who were given the STOP-BANG questionnaire prior to cystoscopy for urologic disease in an ambulatory surgery center. Results . The majority of patients in our study were men (77.7%), over the age of 50 (90.1%), and had BMI < 30 kg/m 2 (88.4%). STOP-BANG results were obtained on 404 patients. Cumulative incidence of the time to discharge between HR and the LR groups was plotted. By 8 hours, LR patients showed a higher cumulative probability of being discharged early (80% versus 74%, P = 0.008 ). Conclusions . Urologic oncology patients at HR for OSA based on the STOP-BANG questionnaire were less likely to be discharged early from the PACU compared to LR patients.